Tumor Treating Fields for Glioblastoma Therapy During the COVID-19 Pandemic - Gatson, Na Tosha N.; Barnholtz-Sloan, Jill; Drappatz, Jan; Henriksson, Roger; Hottinger, Andreas F.; Hinoul, Piet; Kruchko, Carol; Puduvalli, Vinay K.; Tran, David D.; Wong, Eric T.; Glas, Martin (Frontiers in Oncology, 2021)
Background: The COVID-19 pandemic has placed excessive strain on health care systems and is especially evident in treatment decision-making for cancer patients. Glioblastoma (GBM) patients are among the most vulnerable due to increased incidence in the elderly and the short survival time. A virtual meeting was convened on May 9, 2020 with a panel of neuro-oncology experts with experience using Tumor Treating Fields (TTFields). The objective was to assess the risk-to-benefit ratio and provide guidance for using TTFields in GBM during the COVID-19 pandemic. Panel Discussion: Topics discussed included support and delivery of TTFields during the COVID-19 pandemic, concomitant use of TTFields with chemotherapy, and any potential impact of TTFields on the immune system in an intrinsically immunosuppressed GBM population. Special consideration was given to TTFields’ use in elderly patients and in combination with radiotherapy regimens. Finally, the panel discussed the need to better capture data on COVID-19 positive brain tumor patients to analyze longitudinal outcomes and changes in treatment decision-making during the pandemic. Expert Opinion: TTFields is a portable home-use device which can be managed via telemedicine and safely used in GBM patients during the COVID-19 pandemic. TTFields has no known immunosuppressive effects which is important during a crisis where other treatment methods might be limited, especially for elderly patients with multiple co-morbidities. It is too early to estimate the full impact of COVID-19 on the global healthcare system and on patient outcomes and the panel strongly recommended collaboration with existing cancer COVID-19 registries to follow CNS tumor patients.